Simple process capability analysis and quality validation of monoclonal antibody production in bench-top bioreactor - Mel, Maizirwan; Arifin, Mohd Azmir; Kamaruddin, Mohd Hider; Abdul Karim, Mohamed Ismail; Yusof, Faridah (Academic Journals, 2011)
The production of monoclonal antibody (MAbs) for anti-cancer by fermentation of hybridoma cell in bench-top bioreactor was investigated. The main aim of this study was to increase the percentage of cell viability and to achieve high yield of IgM. Many ways can be applied to improve the process and one of them is by choosing the correct six sigma’s design of experiment (DOE). In this study, Taguchi’s experimental design was applied to achieve high percentage of cell viability in the fermentation experiment. The process capability of this study was later analyzed by using the MiniTab Software (Ver. 14). Analysis showed that this study fulfilled a minimum target of process improvement as indicated by the Cp and Cpk value of 0.90 and 0.86. This proved that the fermentation experiment has achieved cell viability of more than 80% throughout the study.